2019
DOI: 10.1371/journal.pone.0220885
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-led medicines’ monitoring in care homes, implementing the Adverse Drug Reaction (ADRe) Profile improvement initiative for mental health medicines: An observational and interview study

Abstract: IntroductionPreventable adverse effects of medicines often pass unnoticed, but lead to real harm.InterventionNurse-led monitoring using the structured Adverse Drug Reaction (ADRe) Profile identifies and addresses adverse effects of mental health medicines.ObjectivesThis study investigated the implementation and clinical impact of ADRe, and barriers to and facilitators of sustained utilisation in routine practice.MethodsAdministration of ADRe was observed for 30 residents prescribed mental health medicines in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 69 publications
1
50
0
Order By: Relevance
“…Alleviation of moral distress after making errors, following up by apologizing to patients and their families [70], standardized tools and feedback [71,72], training regarding communication skills, and coping strategies to reduce nurses' emotional stress [37,73] are considered key leadership roles for nurses. Systematic, in-built support for error identification [19,20] and disclosure should remove the responsibility to inform patients and their families from individual nurses [59]. User-friendly guidelines and reporting mechanisms should be implemented [74,75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alleviation of moral distress after making errors, following up by apologizing to patients and their families [70], standardized tools and feedback [71,72], training regarding communication skills, and coping strategies to reduce nurses' emotional stress [37,73] are considered key leadership roles for nurses. Systematic, in-built support for error identification [19,20] and disclosure should remove the responsibility to inform patients and their families from individual nurses [59]. User-friendly guidelines and reporting mechanisms should be implemented [74,75].…”
Section: Discussionmentioning
confidence: 99%
“…Conditions that could be prevented and safely managed in such settings can lead to hospitalization and increased healthcare costs [18]. In general, residential long-term care settings have been recognized as fertile environments to expand patient safety initiatives, due to the high rate of adverse events [19,20] and institutional barriers to reporting practice errors [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Since many ADRs are preventable, some screening tools have been devised, including Beers' Criteria and the Inappropriate Prescribing in the Elderly Tool (IPET), which augment professionals' clinical judgement in medicine selection and prescription [46]. Profiling the adverse effects of psychotropic medications detects any changes in the patient following PRN administration [47,48]. Additionally, medicine reviews and checks for drug interactions, cautions, and doses have been suggested, including the Screening Tool of Older Persons' Potentially Inappropriate Prescriptions (STOPP) [27,49], the Screening Tool to Alert to Right Treatment (START) [49,50] for older people, and the Norwegian General Practice (NORGEP) tool [51] for those under 71 years.…”
Section: Discussionmentioning
confidence: 99%
“…Prescription and administration of PRN psychotropic medications should not expose patients to the feelings of inferiority and coercion [3]. Since the decision-making process regarding PRN management is complex [11,12], there is a need for a decision support tool for PRN medicines management to prevent medication-related harm in long-term care settings: this should encompass systematic checks for the signs and symptoms of ADRs [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation